Crop-animal research perspectives - Li Pun, H.H. (International Livestock Research Institute, 2000)
This paper starts with an outline on the role of crop-animal systems in rural development; and then looks into systems research and ecoregional research. Under the systems research, it examines why problems of small farmers are complex, and lessons learned including benefits and steps. It then gives a detailed definition of ecoregional research, and summarises the differences between farming systems research (FSR) and ecoregional research (ECOR). The paper ends with a summary on the progress in globalisation and an outlook.